Political Gimmicks on Social Media in the 2024 Presidential Election and Criticism of Democratic Practices in Indonesia: Gimik Politik di Media Sosial Pada Pilpres 2024 dan Kritik Terhadap Praktik Demokrasi di Indonesia - Rahmat, Felisianus Novandri; Gasa, Frederick Masri; Rusdin, Febi Ramadhani; Marut, Yohanes BP (Universitas Muhammadiyah Sidoarjo, 2025)
The contestation of presidential elections in Indonesia is inseparable from the evolving political dynamics, including the 2024 election, which was marked by the widespread use of political gimmicks. All presidential and vice-presidential candidates employed light, casual, and entertaining communication strategies rather than conveying their visions, missions, and policy programs substantively. This phenomenon poses a risk of diminishing the quality of democracy, as political contests tend to favor candidates who can emotionally engage the public rather than those who offer concrete solutions to national issues. This study aims to examine the impact of political gimmicks on the quality of political communication and to propose strategic responses to this trend. A qualitative descriptive approach was employed through a literature review, utilizing sources from scholarly articles and online news platforms. The findings indicate that political gimmicks were predominantly targeted at young voters, who constituted the majority demographic in the 2024 election, making them an effective yet risky campaign tool. Political gimmicks have been shown to obscure political substance, erode democratic values, and hinder the development of a civil society. Therefore, concrete measures are necessary, such as strengthening public political education, utilizing social media as a platform for idea-based contestation, and fostering a collective commitment among candidates, voters, and state institutions to build ethical, transformative, and welfare-oriented political communication.